The bioactivities of fractions from the ethanol extract of Leucosyke capitellata ("Alagasi") leaves - Uy, Mylene M.; Campecino, Arjielyn M. (2015)
The study establishes the toxicities, antioxidant pr and antimicrobial activities of the hexane (LcH), chloroform (LcC), and aqueous (LcA) fractions of the ethanol extract of Leucosyke capitellata leaves. Assessment of the toxicity of the fractions of L.capitellata done using the brine shrimp lethality test showed that all fractions were considered inactive since not one of the fractions was able to kill half of the population of the brine shrimp. Meanwhile, among the three fractions, te LcA fraction consistently exhibited the highest antioxidant properties. The antimicrobial assay showed that fractions LcA and LcC exhibted partial antibacterial activity against B. subtilis and S. aureus. For the antifungal activities, both LcH and LcA were active against C. albicans.
Keywords: Medicinal plants; Classification of plants; Toxicology; Antioxidants